2012
DOI: 10.1038/cmi.2012.41
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pim2-prolonged skin allograft survival through the apoptosis regulation pathway

Abstract: Recently, apoptosis has been considered to be an important regulator for allograft survival. The serine/threonine kinase Pim2 has been implicated in many apoptotic pathways. In a previous study, we found that pim2 was highly expressed in CD4 1 T cells in an allograft model. Here, we further investigated the effects of Pim2 on allograft survival and the underlying mechanisms associated with apoptosis. The results showed that pim2 was overexpressed in grafts and spleens, particularly in spleen CD41 T cells when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…7b); in particular, Ad/HO-1/BMMSC treatment significantly decreased cell apoptosis in the graft mucosa. Acute rejection is associated with increased apoptosis in the graft [36, 37]. The amount of apoptotic body in crypts was one of the criteria for diagnosing the grade of acute rejection in SBTx [35].…”
Section: Resultsmentioning
confidence: 99%
“…7b); in particular, Ad/HO-1/BMMSC treatment significantly decreased cell apoptosis in the graft mucosa. Acute rejection is associated with increased apoptosis in the graft [36, 37]. The amount of apoptotic body in crypts was one of the criteria for diagnosing the grade of acute rejection in SBTx [35].…”
Section: Resultsmentioning
confidence: 99%
“…Pim-2, a Pim family kinase, is found in alloreactive effector T cell and favors its survival and proliferation [62]. It was reported that the Pim-2 level was positively correlated with the severity of allograft rejection and that inhibition of Pim-2 prevented the rejection [63]. Interestingly, T cell regulation, which leads to immune tolerance, is found to be associated with autophagy.…”
Section: Autophagy In Human Immune-related Renal Diseasesmentioning
confidence: 99%
“…Our preliminary work also indicates that CD4 1 CD25 1 Tregs are associated with generegulated allorejection. 2 Ectopic expression of Foxp3 in mouse CD4 1 T cells induces the generation of nTregs in vitro [3][4][5] that results in a developmental transition to a suppressor cell phenotype, such as CD4 1 CD25 2 Foxp3 1 cells, which have been shown to be immune response suppressive. 6 Therefore, Foxp3 is considered a definitive lineage marker of nTregs.…”
Section: Introductionmentioning
confidence: 99%